1993
DOI: 10.1007/bf01299899
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between cystic duct diameter and the presence of cholelithiasis

Abstract: We sought to measure cystic duct diameter in patients without biliary calculi and in those with cholelithiasis or choledocholithiasis. Using endoscopic retrograde cholangiopancreatography (ERCP), we visualized the cystic duct in 168 patients referred to our unit. These patients were distributed into three groups based on findings at ERCP: Group I (N = 57), no calculi in the gallbladder or common bile duct; group II (N = 27), stones found in the gallbladder but absent from the common bile duct; and group III (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…The pathophysiological functions of cystic duct and its contribution to the genesis of cholelithiasis have been discussed extensively over the years (Lichtenstein and Ivy, 1937;Scott and Otto, 1979;Otto et al, 1979;Pitt et al, 1981Pitt et al, ,1982Doty et al, 1983;and Sharp et al, 1990). Recent investigations have pointed out that cholelithiasis is related to abnormal cystic duct configurations (Bornman et al, 1988;Shaw et al, 1993;Kubota et al, 1993;Castelain et al, 1993;Caroli-Bosc et al, 1997;Deenitchin et al, 1998). In particular, Deenitchin et al (1998) showed that, statistically, subjects with gallstones had longer or narrower cystic ducts than those without.…”
Section: Introductionmentioning
confidence: 99%
“…The pathophysiological functions of cystic duct and its contribution to the genesis of cholelithiasis have been discussed extensively over the years (Lichtenstein and Ivy, 1937;Scott and Otto, 1979;Otto et al, 1979;Pitt et al, 1981Pitt et al, ,1982Doty et al, 1983;and Sharp et al, 1990). Recent investigations have pointed out that cholelithiasis is related to abnormal cystic duct configurations (Bornman et al, 1988;Shaw et al, 1993;Kubota et al, 1993;Castelain et al, 1993;Caroli-Bosc et al, 1997;Deenitchin et al, 1998). In particular, Deenitchin et al (1998) showed that, statistically, subjects with gallstones had longer or narrower cystic ducts than those without.…”
Section: Introductionmentioning
confidence: 99%
“…Castelain et al (1993) found that increasing diameter of the duct correlated with increasing severity of gallstone disease, possibly as a result of migration of small stones from the gallbladder causing distension in the duct. Patients without stones had the smallest diameter ducts, followed by those with stones only in the gallbladder.…”
Section: Discussionmentioning
confidence: 96%
“…For example, a low, left-sided entry of the CD into the BD is associated with gallstone disease (Bornman et al, 1988;Caroli-Bosc et al, 1997). In adults, Castelain et al (1993) failed to show an association between a narrow CD and cholelithiasis but Deenitchin et al (1998) found that a longer and narrower CD and a more acute angle between the gallbladder and CD was strongly correlated with the presence of gallstones. Congenital stenosis of the CD has been implicated as an etiologic factor in children (Forshall and Rickham, 1954).…”
Section: Surgical Relevance Of the Cystic Ductmentioning
confidence: 98%
“…It conveys bile to and from the gall bladder. In adults, the CD has a variable length (5-90 mm) and luminal diameter (2.6 Ϯ 0.7 mm) (Lichtenstein and Ivy, 1937;Castelain et al, 1993) but it is typically 2-4 cm long. Its course is frequently tortuous.…”
Section: Gross Anatomymentioning
confidence: 99%